Accountability as The Key to Success: The Effect of Village Funds and Village Fund Allocations on Village Development Performance in Bojonegoro Regency in 2024 (E-Jurnal Akuntansi, 2026)
This study aims to analyze the influence of Village Funds and Village Fund Allocations on Village Development Performance with Accountability as an intervening variable in Bojonegoro Regency in 2024. The research is motivated by the large allocation of village funds that has not optimally improved development performance, making accountability important in fund management. This study uses path analysis with secondary data obtained from village government documents and APBDes realization reports. The results indicate that Village Funds, Village Fund Allocations, and Accountability do not affect Village Development Performance. However, Village Funds and Village Fund Allocations significantly affect Accountability. In addition, Accountability is unable to mediate the influence of Village Funds and Village Fund Allocations on Village Development Performance. These findings show that large village funds do not guarantee improved development performance without good governance and accountability. Therefore, strengthening accountability is essential to support effective village fund management and sustainable village development.
Keywords: Village Funds; Village Fund Allocation; Accountability; Village Development Performance; Village Governance